Imaging Bronchopulmonary Dysplasia—A Multimodality Update - Semple, Thomas; Akhtar, Mohammed R.; Owens, Catherine M. (Frontiers in Medicine, 2017)
Bronchopulmonary dysplasia is the most common form of infantile chronic lung disease and results in significant health-care expenditure. The roles of chest radiography and computed tomography (CT) are well documented but numerous recent advances in imaging technology have paved the way for newer imaging techniques including structural pulmonary assessment via lung magnetic resonance imaging (MRI), functional assessment via ventilation, and perfusion MRI and quantitative imaging techniques using both CT and MRI. New applications for ultrasound have also been suggested. With the increasing array of complex technologies available, it is becoming increasingly important to have a deeper knowledge of the technological advances of the past 5–10 years and particularly the limitations of some newer techniques currently undergoing intense research. This review article aims to cover the most salient advances relevant to BPD imaging, particularly advances within CT technology, postprocessing and quantitative CT; structural MRI assessment, ventilation and perfusion imaging using gas contrast agents and Fourier decomposition techniques and lung ultrasound.